Pengaruh Pastoral Care terhadap Keterlibatan Umat dalam Tugas Diakonia - Floriana Doa; Intan Sakti Pius X (Jurnal Pendidikan Agama dan Teologi, 2024)
This research aims to determine the influence of pastoral care on the involvement of people in diaconal duties. The research method used is a qualitative method through in-depth interviews with several sources involved in diakonia tasks. The research results show that pastoral care has a significant role in increasing people's awareness of the call to serve, providing the skills and knowledge needed to carry out diaconal duties effectively. Pastoral care acts as the main bridge in carrying out Christ's mission to gather those who need service. Through pastoral care, people feel restored in their faith, receive spiritual and practical support, and become involved in church services. Although this goal is sometimes difficult to achieve, pastoral care can increase people's involvement in diaconal duties with direct impacts in the form of growth in faith, new awareness, personality development, and optimism in living life. However, the influence of pastoral care on community involvement is not yet visible, because there are other influencing factors. Suggestions from this research are the need to further increase people's understanding of pastoral care, strengthen personal relationships between pastors and people, and develop spiritual education programs to understand the importance of diakonia and encourage active involvement in church services.